Helping familiar strangers : refugee diaspora organizations and humanitarianism - Olliff, Louise (Worlds in crisis., 2022)
"Who helps in situations of forced displacement? How and why do they get involved? In Helping Familiar Strangers, Louise Olliff focuses on one type of humanitarian group, refugee diaspora organizations (RDOs), to explore the complicated impulses, practices, and relationships between these activists and the "familiar strangers" they try to help. By documenting findings from ethnographic research and interviews with resettled and displaced persons, RDO representatives, and humanitarian professionals in Australia, Switzerland, Thailand, and Indonesia, Olliff reveals that former refugees are actively involved in helping people in situations of forced displacement and that individuals with lived experience of forced displacement have valuable knowledge, skills, and networks that can be drawn on in times of humanitarian crisis. We live in a world where humanitarians have varying motivations, capacities, and ways of helping those in need, and Helping Familiar Strangers confirms that RDOs and similar groups are an important part of the tapestry of care that people turn to when seeking protection far from home"--